Penentuan kualitas mutu air sungai Kampwolker Jayapura dengan metode STORET - Wiher Haeraty; Auldry Fransje Walukouw (Universitas Riau, 2022)
The condition of the waters in Papua is that there are various kinds of marine life in the body of water. One of the water bodies is the Kampwolker River which has a length of 14.15 m with an intlet river (a river that empties into Lake Sentani) which is located in the Kampwolker River watershed to Jl. 2 Expo Arena, Waena. It turns out that the Kampwolker River has a heavily polluted result with a score of 48. GPS and Arcgis Software Version 10.3 show three locations of the Kampwolker river, including: the intake Kampwolker River, the middle Kampwolker River, and the downstream Kampwolker River. Water quality was measured using the STORET method. Analysis of water samples obtained several samples of the most dominantly high chemical parameters, including Phosphate (PO4 – P) of 2.48 mg/l, Copper (Cu) of 0.235 mg/l, and Lead (Pb) of 0.15 mg/l. l. Kampwolker river pollution shows a color change to brown. This is due to the activities of densely populated community settlements, the agricultural industry, mineral C mining, and other industrial fields. Floods and erosion occur due to the ignorance of the community around the Kampwolker river to the importance of ecosystems and drinking water sources for the survival of the people in Jayapura City.